Experiences of Elder Mistreatment: A Latent Profile Analysis - Chokkanathan, Srinivasan (Journal of interpersonal violence, 2021)
Using a polyvictimization framework, this study seeks to identify profiles of older adults who are mistreated by their family members. Data were drawn from a survey (n = 897) on the prevalence of elder mistreatment in rural India. This study involved 187 community-dwelling older adults (aged 61 years and above) with experiences of mistreatment in the year prior to the interview. Mistreatment was assessed through an adapted version of the Conflict Tactics Scale. Latent profile analysis was conducted to classify older adults into empirically derived clusters. The best fitting model yielded three distinct profiles: multiple mistreatment all (high frequency), multiple mistreatment (predominantly psychological), and multiple mistreatment (predominantly neglect). The three clusters differed in terms of individual, familial, and perpetrator characteristics. These findings highlight the heterogeneity of elder mistreatment experiences and the need for specific interventions that address the needs of mistreated older adults.